2016
DOI: 10.1093/mnras/stw1088
|View full text |Cite
|
Sign up to set email alerts
|

Supernova 2014J at M82 – II. Direct analysis of a middle-class Type Ia supernova

Abstract: We analyze a time series of optical spectra of SN 2014J from almost two weeks prior to maximum to nearly four months after maximum. We perform our analysis using the SYNOW code, which is well suited to track the distribution of the ions with velocity in the ejecta. We show that almost all of the spectral features during the entire epoch can be identified with permitted transitions of the common ions found in normal SNe Ia in agreement with previous studies.We show that 2014J is a relatively normal SN Ia. At ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…No such signatures were detected for SNe 1998bu and 2000cx (Lundqvist et al 2013), SN 2001el (Mattila et al 2005, SNe 2005am and 2005cf (Leonard 2007), SN 2012cg , SN 2013gy (Holmbo et al 2018), or SN 2017cbv (Sand et al 2018, nor were they detected by Graham et al (2017) in 8 other SNe Ia. The nearby SNe Ia 2011fe and 2014J were particularly well-studied events (Brown et al 2012;Munari et al 2013;Mazzali et al 2014;Foley et al 2014;Goobar et al 2014;Galbany et al 2016;Vallely et al 2016;Dhawan et al 2018), but they too showed no hydrogen emission in their late-time spectra Lundqvist et al 2015;Sand et al 2016).…”
Section: Introductionmentioning
confidence: 97%
“…No such signatures were detected for SNe 1998bu and 2000cx (Lundqvist et al 2013), SN 2001el (Mattila et al 2005, SNe 2005am and 2005cf (Leonard 2007), SN 2012cg , SN 2013gy (Holmbo et al 2018), or SN 2017cbv (Sand et al 2018, nor were they detected by Graham et al (2017) in 8 other SNe Ia. The nearby SNe Ia 2011fe and 2014J were particularly well-studied events (Brown et al 2012;Munari et al 2013;Mazzali et al 2014;Foley et al 2014;Goobar et al 2014;Galbany et al 2016;Vallely et al 2016;Dhawan et al 2018), but they too showed no hydrogen emission in their late-time spectra Lundqvist et al 2015;Sand et al 2016).…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, observational evidence for such progenitor systems has proven to be elusive. The nearby SNe Ia 2011fe and 2014J were particularly well-studied (Brown et al 2012;Munari et al 2013;Mazzali et al 2014;Foley et al 2014;Goobar et al 2014;Galbany et al 2016;Vallely et al 2016;Shappee et al 2017;Yang et al 2018), but no compelling evidence was found for the existence of non-degenerate companions Chomiuk et al 2012;Shappee et al 2013;Margutti et al 2014;Lundqvist et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…SN 2014J in M82 is one of the nearest SN Ia in decades and has been extensively studied (e.g. Kelly et al 2014;Diehl et al 2014;Foley et al 2014;Ashall et al 2014;Vacca et al 2015;Galbany et al 2016;Vallely et al 2016). It is heavily reddened by host galaxy dust, but shows spectral features of a normal SN Ia (Amanullah et al 2014).…”
Section: Introductionmentioning
confidence: 99%